No separate spheres: the contingent reproduction of living labor in Southern Africa. Issue 6 (21st November 2022) - O'Laughlin, Bridget
Abstract: Social Reproduction Theory (SRT) rejects the classical political economy distinction between productive and unproductive labor, the latter defined as all labor that does not produce surplus-value. Rather, much non-commodified labor, particularly that done in the domestic sphere, is not unproductive but necessary since it produces labor-power. Hence, SRT has proposed an alternative distinction: productive versus reproductive spheres of labor. This article argues that this opposition too is analytically and politically misleading. Capital is concerned with profit, not with the reproduction of the living labor within which labor-power is always embedded. It is the everyday struggles of living labor that determines its reproduction. These take place not just in the kin-based sphere of the family but in overlapping, shifting places and processes, including struggles for better wages and working conditions in capitalist firms. This paper uses two different contexts in southern Africa to make this argument: an influential debate over how to understand changes in apartheid in South Africa in the 1970s; and a sugar-cane plantation in Mozambique where interdependent contradictions of class, gender and race defined a social division of labor that systematically compromised the reproduction of living labor.